Learning Quantities and Units in Elementary Schools - Nikadinata, Vivian; Aena, Anisa Nur; Oktafianti, Atikah Anjani; Kurniawati, Wahyu (Sean Institute, 2024)
Quantities and units are the main foundation in physics, forming an inseparable basis for understanding more complex physical concepts. This article explores various aspects of quantities and units, starting from basic quantities, derived quantities, to vector and scalar quantities. The discussion covers measurement topics, measurement techniques, units, international systems of units, and dimensions. The importance of quantities and units is not only as technical terminology, but as an integral component for measuring and conveying natural phenomena with precision. This article aims to provide comprehensive insight into the concept of quantity, from basic to complex, as well as applying this concept in measurement and scientific communication. Literature research methods are used to detail the main concepts of quantities and units. The results and discussion discuss types of quantities, basic quantities, derived quantities, and the role of the international system of units. The article also touches on measurements, dimensions, and research methods. In conclusion, a deep understanding of quantities and units provides a solid foundation for accurate measurement and effective communication in the physical sciences.